2012
DOI: 10.3109/0886022x.2012.687347
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Quercetin on Sodium Fluoride-Induced Oxidative Stress in Rat’s Kidney

Abstract: Objective: The in vivo nephroprotective effect of quercetin against sodium fluoride (NaF)-induced damage was studied. Methods: Renal injury was induced by daily administration of NaF (600 ppm) through drinking water for 1 week. The levels of reduced glutathione (GSH), lipid peroxidation as well as superoxide dismutase and catalase activity of kidney homogenates were determined. The serum markers of glomerular damage, including creatinine, serum urea, and blood urea nitrogen levels, were also assessed. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…The present results are in accordance with previous fl uorosis reports [3,13,19]. Decrease in the level of fl uoride after mitigation with leaf extract also resulted in signifi cant increase in content of reduced glutathione as compared with 40 days of fl uoride treatment.…”
Section: Catalase (Cat)supporting
confidence: 93%
See 1 more Smart Citation
“…The present results are in accordance with previous fl uorosis reports [3,13,19]. Decrease in the level of fl uoride after mitigation with leaf extract also resulted in signifi cant increase in content of reduced glutathione as compared with 40 days of fl uoride treatment.…”
Section: Catalase (Cat)supporting
confidence: 93%
“…It was observed that sodium fl uoride exposure in rats caused a signifi cant (p<0.001) decrement in total activity of superoxide dismutase, catalase, and glutathione peroxidase. This fi ndings are in accordance with [13,15,16,22]. Boerhaavia diff usa L. leaf extract administration signifi cantly (p<0.001) accelerated the renal activities of superoxide dismutase, catalase, and glutathione peroxidase in fl uoridated rats kidney tissue.…”
Section: Catalase (Cat)supporting
confidence: 86%
“…Calycosin promotes angiogenesis via activation of MAPK with the involvement of ERK1/2 and ER [94]. The degree node of quercetin from CS was 4, which is from its antioxidant that protects renal function [95].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, the water extract showed antioxidant activity comparable with the methanol extract (p > 0.05). The validation of antioxidant potential of herbal medicines in our laboratories is based on several in-house in vitro cell-free and cell-based assays [33][34][35][36][37][38][39][40][41][42][43][44] as well as in vivo models [45][46][47][48][49][50][51][52][53][54]. Since the principal active constituent of the methanol and water extracts of M. stenopetala leaves is the well-characterised antioxidant and bioactive agent rutin, further biological bioassays on the extracts were not necessary.…”
Section: Methodsmentioning
confidence: 99%